SURFACE PLASMON RESONANCE STUDY OF THE INTERACTION BETWEEN THE HUMAN TATA-BOX BINDING PROTEIN AND THE TATA ELEMENT OF THE NOS2A GENE PROMOTER - I. A. Drachkova; S. V. Shekhovtsov; S. E. Peltek; P. M. Ponomarenko; T. V. Arshinova; M. P. Ponomarenko; T. I. Merkulova; L. K. Savinkova; N. A. Kolchanov (Вавиловский журнал генетики и селекции, 2014)
Interaction ofthe TATA-binding protein (ТВР) with the TATA box and formation ofthe TBP/TATA complex is the first step in the transcription complex assembly and the central event in transcription regulation. It is known that some single nucleotide polymorphisms (SNPs) in the human TATA box and its flanks are associated with elevated risk ofvarious disorders (Savinkova etal., 2009). Little is known about changes in the TBP/TATA interaction leading to the elevated risk ofany disease. Thus, we have studied the influence ofSNP (–21 t > c), adjoining to the TATA box ofthe NOS2A promoter, on the interaction by surface plasmon resonance (SPR) on biosensor ProteOn XPR36 (BioRad). The sensograms obtained in the experiment indicate that the constant for the interaction with TATA bearing SNP –21 t > c differ little from the constant with the wild-type box and the dissociation constants differ approximately twofold. Experiments utilizing the SPR method and classical EMSA have shown that ТВР immobilization on the microchip dextran surface does not alter its affinity to TATA-containing oligonucleotides.